Soil carbon sequestration to mitigate climate change - Lenka, Narendra Kumar; Lenka, Sangeeta; Biswas, A. K. (Indian Farming, 2016)
There are two categories of mitigation methods in agriculture: carbon sequestration in soils and emission reductions. The emission reductions or abatement in context of agriculture, may be on-farm or offfarm. The on-farm abatement strategies include reducing emissions through appropriate soil, manure and crop management methods, where as the off-farm strategy is considered to be replacement of fossil fuels through production of cleaner-burning bioenergy, such as ethanol, biogas, and methane, which can be derived from agricultural production.